Adinkra Symbols and Political Communication: Analysing President John Mahama’s Inaugural Apparel on 7th January, 2025. - Horsu, Isaac; Opare, De-Love Anobah; Amankwah , Adwoa Sikayena; Kyei, Emmanuel (International Journal of Language and Literary Studies, 2025)
Adinkra Symbols and Political Communication: Analysing President John Mahama’s Inaugural Apparel on 7th January, 2025. Isaac Horsu, PhD1, De-Love Anobah Opare 2, Adwoa Sikayena Amankwah, PhD3, Emmanuel Kyei, PhD 4 1 ,2&3 Department of Communication Studies, University of Professional Studies, Accra, Ghana 4 Department of Interdisciplinary Studies, Akenten Appiah-Menka University of Skills Training and Entrepreneurial Development, Mampong, Ghana ???? email: ekyei@aamusted.edu.gh ABSTRACT The Akan people view Adinkra symbols as metaphoric expressions of their experiences, embodying their cultural identity. The study focused on how Akan Adinkra symbols serve as a means of communication in the socio-political context of Ghana. The study explored the meaning of the adinkra symbols printed in President John Dramani Mahama's apparel during his inaugural ceremony on the 7th of January, 2025 as the President of Ghana. The study qualitatively analysed the symbols, highlighting their socio-political implications to show how they communicate in the political atmosphere. Framed as a visual rhetorical analysis, the research highlights the representation of Ghanaian culture and identity through Adinkra symbols, demonstrating their relevance beyond traditional contexts and into socio-political discourse. The study concludes that President John Dramani Mahama's selection of Adinkra symbols for his inaugural apparel was a persuasive act of visual rhetoric, symbolising unity, resilience, and divine guidance for Ghana's future. The study enhances critical thinking and raises awareness of the importance of visual rhetoric in socio-political engagement and advocacy.